2018
DOI: 10.1016/bs.ctdb.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Fibril Assembly and Function

Abstract: Collagen fibrils are the major mechanical component in the extracellular matrix of a broad range of multicellular animals from echinoderms to vertebrates where they provide a stable framework for tissues. They form the key tension-resisting element of a complex fiber-composite system that has a tissue-specific hierarchical structure linked to mechanical demands. Remarkably, these tissues are self-maintaining and avoid fatigue failure over the lifetime of the animal. Collagen fibrils can assemble spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 127 publications
3
128
0
1
Order By: Relevance
“…Many secreted matrix proteins are packaged and trafficked via specialized vesicles. For example, collagens are secreted from extra-large vesicles (Malhotra & Erlmann, 2015) and then processed after secretion to enable their assembly (Holmes, Lu, Starborg, & Kadler, 2018).…”
Section: Apical Matrix May Generate Counteract and Distribute Multipmentioning
confidence: 99%
“…Many secreted matrix proteins are packaged and trafficked via specialized vesicles. For example, collagens are secreted from extra-large vesicles (Malhotra & Erlmann, 2015) and then processed after secretion to enable their assembly (Holmes, Lu, Starborg, & Kadler, 2018).…”
Section: Apical Matrix May Generate Counteract and Distribute Multipmentioning
confidence: 99%
“…Such analysis implies that the reduction of the ratio parameter values at higher grades of tumor progression, observed in Figure 5B, could not be attributed to the f, δ angle orientation disorders, indicating that different morphological modifications of the collagen structure occur after the that the focal volume is~3 μm 3 and includes 100 fibrils with mean diameter and length in the order of 200 nm and 1 μm respectively. 53,54 This is considered to be a good approximation for the focusing conditions that were employed (N.A. = 0.8).…”
Section: Resultsmentioning
confidence: 99%
“…Collagen is the main structural element of the extracellular matrix of connective tissues, important for force transmission and load-bearing. 26 The morphology of the fibrils and the architecture of collagen fibril networks vary widely among tissues, providing tissue-specific mechanical functions. Reconstitution studies have shown that collagen assembly is regulated by many environmental factors, such as temperature, pH, and ionic strength.…”
Section: Structural Analysis Of More Complex Fibril-forming Systemsmentioning
confidence: 99%
“…The absence of these telopeptides results in a loss of diameter uniformity and changes in the fibril assembly pathway. 26,31 Fibrils reconstituted from purified collagen usually exhibit high axial periodicity, but their degree of lateral packing order is still elusive. X-ray diffraction studies in tissue collagen indicate an almost crystalline molecular packing, 27,29,32 but deviations from this model are often observed.…”
Section: Lateral Assembly and Fibril Packingmentioning
confidence: 99%
See 1 more Smart Citation